Introduction to Biosystems Engineering - Holden, Nicholas M.; Wolfe, Mary Leigh; Ogejo, Jactone A.; Cummins, Enda J. (Open textbook library., 2021)
The discipline of Biosystems Engineering emerged in the 1990s from the traditional strongholds of agricultural engineering and food engineering. Biosystems engineering integrates engineering science and design with applied biological, environmental, and agricultural sciences. Introduction to Biosystems Engineering is targeted at 1st and 2nd year university-level students with an interest in biosystems engineering but who are not yet familiar with the breadth and depth of the subject. It is designed as a coherent educational resource, also available for download as individual digital chapters. The book can be used as a localized, customizable text for introductory courses in Biosystems Engineering globally. It is written as a series of stand-alone chapters organized under six major topics: Food and Bioprocessing; Environment; Buildings and Infrastructure; Information and Communications Technology and Data; Machinery Systems; and Energy. Each chapter is organized around stated learning outcomes and describes key concepts, applications of the concepts, and worked examples. Instructors adopting or reviewing this text are encouraged to register with the publisher using this form.